Kapasitas Vital Paru pada Pekerja Tambal Ban Pinggir Jalan - Sari, Juni Arum; Astuti, Rahayu; Prasetio, Diki Bima (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
Background. Level of pulmonary vital capacity (PVC) is the parameter of pulmonary function. Tire repair workers on the side of the highway is the susceptible group to the decreasing of pulmonary function caused by the accumulated of dust and vehicle emission exposure. Aim of this study is to understand the correlation between nutritional status, sport habits, smoking habits, masker use, history of pulmonary diseases, duration and period of work with CVP. Method. This analytic cross sectional study involved 28 tire repair workers on Jalan Mugas Raya Semarang. PVC was measured using spirometer, while nutritional status was calculated by comparing body weight with body height (in meter square). The other variables were measured by interview with questionnaire. Results. Only 39.3% of tire repair workers have normal pulmonary function. It was correlated with nutritional status (p= 0,019), sport (p=0,001) and smoking (p=0,022) habits, history of pulmonary diseases (p=0,041), duration (p=0,019) and period (p=0,016) of work. Multivariate analysis showed that the PVC was determined by the period of work. Conclusion. Majority of the tire repair workers on the side of highway have the abnormal pulmonary function, and necessary to be fostered with the public health action.